DESKRIPSI MISKONSEPSI SISWA DALAM MENYELESAIKAN SOAL TERMOKIMIA PADA SISWA KELAS XI MAN KUBU RAYA - Murniati, Sri; Enawaty, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine misconception of student and to describe the causes of the misconception in thermochemistry material on XI grade of MAN Kubu Raya. This research type is qualitative research with descriptive method.  The sample that used is 19 students. This instrument of this research was diagnostic test that organized as multiple choice with four answer alternative. The most common misconceptions is bond energy concept (92.11%). The least misconceptions are the change in entalphy concept (5.26%) and Hess’s Law concept (5.26%). These results show the student’s misconceptions caused by assosiative thinking student (23.18%), incomplete reasoning (2.65%), intuition thinking (23.84%), preconception (21.85%), ability of student (9.27%), and  interest of student (19.21). Keywords: Descriptive, misconception, diagnostic test, thermochemistry